Intracerebral Hematoma Due to Aneurysm Rupture: Are There Risk Factors Beyond Aneurysm Location?. Issue 6 (June 2016) - Jabbarli, Ramazan; Reinhard, Matthias; Roelz, Roland; Shah, Mukesch; Niesen, Wolf-Dirk; Kaier, Klaus; Taschner, Christian; Weyerbrock, Astrid; Van Velthoven, Vera
Abstract : BACKGROUND: Along with subarachnoid hemorrhage (SAH), a ruptured aneurysm may also cause an intracerebral hematoma (ICH), which negatively impacts the functional outcome of SAH. OBJECTIVE: To identify independent risk factors of aneurysmal ICH. METHODS: Six hundred thirty-two consecutive patients with aneurysmal SAH treated at our institution from January 2005 to December 2012 were eligible for this study. Demographic parameters and preexisting comorbidities of patients, as well as various clinical and radiographic characteristics of SAH were correlated with the incidence and volume of aneurysmal ICH. RESULTS: One hundred fifty-five patients (25%) had ICH on initial computed tomography with a mean volume of 26.7 mL (±26.8 mL). Occurrence and volume of ICH were associated with the location (distal anterior or middle cerebral artery >proximal anterior cerebral or internal carotid artery >posterior circulation, P < .001/ P < .001) and size (>12 mm, P = .026/ P < .001) of the ruptured aneurysm. Vascular risk factors independently increased the risk of ICH as well (arterial hypertension: odds ratio [OR] = 1.62, P = .032; diabetes mellitus: OR = 3.06, P = .009), while the use of aspirin ( P = .037) correlated with the volume of ICH. The predictors of ICH were included into a risk score (0-9 points) that strongly predicted the occurrence of ICH ( P = .01). Poor functional outcome after SAH was independently associated with the occurrence of ICH ( P = .003, OR = 2.77) and its volume ( P = .001, OR = 1.07 per-mL-increase). CONCLUSION: Aneurysmal ICH is strongly associated with poorer functional outcome and seems to be predictable even before the bleeding event. The proposed risk factors for aneurysmal ICH require further validation and may be considered for treatment decisions regarding unruptured intracranial aneurysms. ABBREVIATIONS: ACA, anterior cerebral artery DHC, decompressive hemicraniectomy EVD, external ventricular drainage ICA, internal carotid artery ICH, intracerebral hematoma MCA, middle cerebral artery mRS, modified Rankin scale PC, posterior circulation SAH, subarachnoid hemorrhage SIRS, systemic inflammatory response syndrome TCD, transcranial Doppler sonography Abstract : Supplemental Digital Content is Available in the Text.